KOMPARASI HASIL BELAJAR SISWA DIAJARKAN BERSUSUN PENDEK DAN KALKULATOR AJAIB KELAS IV SDN 16 PONTIANAK - F37008013, Masni; Tampubolon, Budiman; ., Suryani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The Research about comparison study of students study result that be taught with the short series and the miracle calculator on fourth grade of Elementary School 16 in East Pontianak aims to analysis whether there are the different of students study result that be taught with the short series and the miracle calculator on fourth grade of Elementary School 16 in East Pontianak. The method that used is an experiment method. The form of research that used is Queasy Experiment type Nonequivalent Control Group Design. Based on statistic calculation from the average of post-test result from control class was 69,50 and the average of post-test from experiment class was 82,13, obtained ttest the post-test data was 3,578 and ttable (? = 5% and dk = 58) as big as 2,002, then can conclusion that Ha acceptable. It means there is a different of students study result that teaching with the miracle calculator (experiment class) and the data that teaching with the short series (control class). From effect size calculation (ES) retrieved the price of ES =0.82 (high category), it means learn with miracle calculator influential to students study result. Keyword: Comparison study, Study result, the short series, Miracle calculator Abstrak: Penelitian mengenai komparasi hasil belajar siswa diajarkan dengan bersusun pendek dan kalkulator ajaib kelas IV SDN 16 Pontianak Timur bertujuan untuk menganalisis apakah ada perbedaan hasil belajar siswa diajarkan dengan bersusun pendek dan kalkulator ajaib kelas IV SDN 16 Pontianak Timur. Metode yang digunakan adalah metode eksperimen. Bentuk penelitian yang digunakan adalah Quasy Eksperiment dengan jenis The Nonequivalent Control Group Design. Berdasarkan perhitungan statistic dari rata-rata hasil post-test kelas control 69,50 dan rata-rata hasil post-test kelas eksperimen 82,13, diperoleh thitung data post-test sebesar 3,578 dan ttabel (? = 5% dan dk = 58) sebesar 2,002, maka dapat disimpulkan bahwa Ha diterima. Jadi, dapat disimpulkan bahwa terdapat perbedaan hasil belajar siswa yang diajar dengan kalkulator ajaib (kelas eksperimen) dan data yang diajar dengan cara bersusun pendek (kelas kontrol). Kata Kunci: Studi Komparasi, Hasil Belajar, Cara Bersusun Pendek, Kalkulator Ajaib